Hubungan Bullying Terhadap Harga Diri Di Kalangan Anak Remaja Sma Negeri 04 Kota Bengkulu Tahun 2025 - Gita Agustya Indriani; Dilfera Hermiati; Tita Septi Handayani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Bullying is the most common form of harassment among adolescents, linked to emotional and behavioral issues as well as mental health morbidity. According to data published by the KPAI, there were 17 cases of bullying in educational institutions at various levels in 2021, increasing to 21 cases in 2022, and reaching 30 cases in 2023. The KPAI also recorded that from 2011 to 2019, 574 male students and 425 female students were victims of bullying in schools. Other data related to bullying perpetrators also indicate that 440 male students and 326 female students have engaged in bullying behavior at school (Kemen PPA, 2022). The purpose of this study is to determine the relationship between bullying and self-esteem among students at State High School 04 Bengkulu. This research uses a correlational method to determine the strength and direction of the relationship. The sampling technique employed total sampling with a sample size of 129 respondents, who are students of State High School 04 Bengkulu. The results of the univariate analysis show that most of those experiencing bullying fall into the high category, with 28 individuals (21.71%), while self-esteem was categorized as low for 28 respondents (21.71%). The results of the bivariate analysis indicate a relationship between bullying and self-esteem, with a p-value of 0.000 < 0.05, which means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Hı) is accepted, indicating a relationship between bullying and self-esteem among high school students. It is hoped that schools will pay more attention to the issue of bullying occurring in the school environment, as it can trigger low self-esteem